Analysis and Design of Single Phase High Efficiency Transformer less PV Inverter Topology - Jayalakshmi N. S.; Ankit Kumar; Ashish Kumar (Institute of Advanced Engineering and Science, 2018)
An inclination towards renewable energy resources has been increased due to the requirement of clean environment and to satisfy the increasing power demand for the long run. A grid connected system requires the availability of a transformer in its power conversion stages that provides galvanic isolation between the grid and the power system. But inclusion of transformer results in making the system bulky and more expensive. In this paper different transformer-less PV inverter topologies are analyzed by comparing their efficiency, leakage current and THD of load current using MATLAB/Simulink environment. In order to achieve maximum power, maximum power point tracking (P&O algorithm) is used. From the simulation results, modified HB-ZVR is found to have minimum leakage current and constant common mode voltage with higher efficiency. Also, the hardware results are obtained for modified HB-ZVR topology.